PENGARUH PADAT TEBAR TERHADAP KELANGSUNGAN HIDUP DAN LAJU PERTUMBUHAN IKAN MASKOKI (Carassius auratus) YANG DIPELIHARA DENGAN SISTEM RESIRKULASI - Andrius Ginting; Syammaun Usman; Maragunung Dalimunthe (AQUACOASTMARINE, 2014)
Goldfish is the most desirable ornamental. The market demand required intensive cultivation. Intensive cultivation can be done by optimizing stocking density. This study aims to determine the effect of stocking density on survival and growth rate of goldfish (Carassius auratus) as well as to determine the maximum stocking density goldfish with an average length 4,16 cm and average weight 1,84 grams. The experimental design used was Completely Randomized Design (CRD) with three treatments is stocking density 1 fish / liter (P1), 2 fish / liter (P2), and 3 fish / liter (P3) and repeated 3 times. Treatment P1 shows the growth rate of weight daily and length growth rate that equal to the best daily is 2,75% and 0,87%. Stocking density significantly affect the growth rate of the long and weight growth rate daily but did not significantly affect survival. DMRT furthertest results indicate treatments P3 is significantly different from P1.Keywords: Carassius auratus, Goldfish, Growth Rate, Stocking Density, Survival Rate.